Literature Review of Transformational Leadership: A Study of Effective Leadership Strategy - Kartikasari, Retno; Suyoso, Aldo Lovely Arief; Agustina, Tri Siwi (Manunggal Halim Jaya, 2025)
In the Industrial Revolution 4.0 and Society 5.0 era, companies face the challenge of continuously adapting and improving human resource competencies as the key to success. High team member performance is crucial and is influenced by transformational leadership. An in-depth understanding of effective leadership strategies supporting positive organizational transformation is important to study. Although previous research has explored transformational leadership, comprehensive analysis of leadership strategy variables that support transformational leadership effectiveness is still limited. This study seeks to fill this gap by profoundly analyzing the leadership strategy variables that are key to the success of transformational leadership. This study aims to explore and analyze the variables of effective leadership strategies, especially in the context of transformational leadership. This research uses a qualitative approach by reviewing 10 related journals, consisting of 7 national and three international journals, published in the last 5 years (2018-2023). The data processing technique used content analysis to identify and examine leadership strategy variables that support the effectiveness of transformational leadership. The results revealed that effective communication, developing an inspiring vision, empowering employees, and establishing an organizational culture that supports change are key leadership strategy variables in supporting the success of transformational leadership. The findings of this study have important implications for management practitioners and policymakers in developing effective transformational leadership in organizations. Future research can explore the empirical impact of implementing leadership strategy variables on organizational performance.